Dosis Pupuk Fosfat Terhadap Pertumbuhan dan Hasil Beberapa Jagung Hibrida - Herlina Mega Puspitasari; Ahmad Yunus; Dwi Harjoko (Agrosains : Jurnal Penelitian Agronomi, 2018)
Corn (Zea mays) is a primary source of food after rice, considered as cerealia crops. This research to analyzing about growth and yield of several variety of hybrid corn on phospat fertilizer dosage giving because in Indonesia the land is nutrient-deficient phospat. This research has been held on June until October 2017 in Kecamatan Piyungan, Kabupaten Bantul, Daerah Istimewa Yogyakarta. Plan which used in this research are Split Plot Design which consist of 2 factors which observed three varieties of hybrid corn (ABCD, EFGH and IJKL) as main plot and phospat fertilizer dosage giving (0, 100 and 150 kilogram ha)  as  sub plot which repeated three times. Research fact found that the topography of the research field is 40% of the plains with a slope of less than 2% and 60% of hilly areas with a slope above 40.1% and the type of the soil is regosol with the highest temperature recorded at the study site was 32ºC with the lowest temperature of 23ºC, then phospat fertilizer dosage is strongly influence the growth and yield of each hybrid corn variety. The best dosage of fosfat fertilizer for corn growth is 150 kilogram ha on each variety, which are ABCD variety, EFGH, and IJKL. The best habit of the growth and yield of hybrid corn is on the phospat fertilizer dosage giving at 150 kilogram ha with variety EFGH.